2017
DOI: 10.1042/cs20170157
|View full text |Cite
|
Sign up to set email alerts
|

Role of the Nrf2/HO-1 axis in bronchopulmonary dysplasia and hyperoxic lung injuries

Abstract: Bronchopulmonary dysplasia (BPD) is a chronic illness that usually originates in preterm newborns. Generally, BPD is a consequence of respiratory distress syndrome (RDS) which, in turn, comes from the early arrest of lung development and the lack of pulmonary surfactant. The need of oxygen therapy to overcome premature newborns' compromised respiratory function generates an increasing amount of reactive oxygen species (ROS), the onset of sustained oxidative stress (OS) status, and inflammation in the pulmonary… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
34
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 60 publications
(35 citation statements)
references
References 98 publications
1
34
0
Order By: Relevance
“…HO‐1 expression is enhanced by transcription factors, Nrf2, and is suppressed by transcriptional repressor, Bach1 . The present study revealed that LIR induced Nrf2 upregulation but Bach1 downregulation.…”
Section: Discussionsupporting
confidence: 51%
“…HO‐1 expression is enhanced by transcription factors, Nrf2, and is suppressed by transcriptional repressor, Bach1 . The present study revealed that LIR induced Nrf2 upregulation but Bach1 downregulation.…”
Section: Discussionsupporting
confidence: 51%
“…Moreover, a higher percentage of PBMΦ-IL10 upregulated HO-1 after EL challenge, suggesting a CD163 driven signaling to anti-inflammatory polarisation in adults, which is diminished in newborns. CD163 dependent HO-1 regulation could be a target for therapeutic strategies, since HO-1 reduces oxidative stress, which is one of the main triggers for bronchopulmonary disease (BPD) 41 .…”
Section: Discussionmentioning
confidence: 99%
“…Among these enzymes, HO‐1 is an important enzyme involved in a variety of pathologies . The Nrf2/HO‐1 signalling is one of the most promising therapeutic targets for several diseases, including renal I/R injury . Our results showed that AR induced the activation of Nrf2/HO‐1 pathway in H/R‐stimulated HK‐2 cells, and knockdown of Nrf2 reversed the renal‐protective effects of AR on HK‐2 cells.…”
Section: Discussionmentioning
confidence: 99%